PREPARATION OF SPRAY DRIED COAMORPHOUS SOLIDS TO IMPROVE THE SOLUBILITY AND DISSOLUTION RATE OF ATORVASTATIN CALCIUM (Jurnal Teknologi (Sciences & Engineering), 2021)
Atorvastatin calcium (AC) is a statin drug used to lower cholesterol. Its crystalline form is usually found in the market with low solubility properties. The amorphization of crystalline AC is a technique used to increase its solubility however; the amorphous form has less thermodynamic stability. Therefore, to increase the solubility properties of its crystalline form, an AC coamorphous solid was prepared. This coamorphous solid was prepared using spray drying techniques, and coformers such as isonicotinamide (INA) and maleic acid (MA). Furthermore, characterization was carried out using powder X-ray diffraction, differential scanning calorimetry, fourier transform infrared spectroscopy, and scanning electron microscopy, while the solubility properties test was conducted using the shake-flask and paddle method. The results showed that the spray-dried solids were coamorphous with single-phase homogeneous systems. Furthermore, the coamorphous solids, AC-INA and AC-MA were found to have a higher Tg than the melting points of other components, and formed intermolecular interactions between them. The higher Tg and presence of intermolecular interactions indicate that coamorphous solids are more stable than the amorphous form. Therefore, the results of the solubility and dissolution test showed that the coamorphous solid of AC-INA and AC-MA have better solubility properties compared to the AC crystalline form.